In, Against and Beyond Precarity: Work in Insecure Times. (June 2018) - Alberti, Gabriella; Bessa, Ioulia; Hardy, Kate; Trappmann, Vera; Umney, Charles
In this Foreword to the special issue 'In, Against and Beyond Precarity' the guest editors take stock of the existing literature on precarity, highlighting the strengths and limitations of using this concept as an analytical tool for examining the world of work. Concluding that the overstretched nature of concept has diluted its political effectiveness, the editors suggest instead a focus on precarization as a process, drawing from perspectives that focus on the objective conditions, as well as subjective and heterogeneous experiences and perceptions of insecure employment. Framed in this way, they present a summary of the contributions to the special issue spanning a range of countries and organizational contexts, identifying key drivers, patterns and forms of precarization. These are conceptualized as implicit, explicit, productive and citizenship precarization. These forms and patterns indicate the need to address precariousness in the realm of social reproduction and post-wage politics, while holding these in tension with conflicts at the point of production. Finally, the guest editors argue for a dramatic re-think of current forms of state and non-state social protections as responses to the precarization of work and employment across countries in both the Global 'North' and 'South'.